The Effect of Plastic Waste as Soil Stabilizer - A S Abdul Rahman, Mohamed Ahmed Hafez, N Sidek, A M Murozi (Mathematical Statistician and Engineering Applications, 2022)
In recent years, stabilisers such as lime, cement and fly ash have become prohibitively expensive for soil stabilisation. In some circumstances, solid waste production, particularly garbage from plastic products, is increasing uncontrollably and continuously. Given the rapid increase in plastic waste and the rising expense of additives in recent years, the current study focuses on treating the soil with plastic waste as a soil stabiliser to enhance the soil’s bearing capacity. This prospective study aimed to determine the index properties, review past research on the engineering properties and develop a hypothesis on the optimum proportion of plastic waste to be employed in the soil for engineering applications. This research paper examines the use of plastic waste from polyethene terephthalate (PET) plastic bottle shreds as a stabiliser, which necessitates a review of previous research studies and several investigations following the British Standard (BS), such as dry and wet sieving, hydrometer test, oven-drying method, density bottle method, Atterberg limit tests, compaction test and finally direct shear test. The study devised a hypothesis for the ideal percentage of plastic waste in the soil, which was 2%. The inclusion of 2% plastic waste was likely to boost soil strength. Furthermore, the shreds acted as reinforcements, helping to enhance the soil structure. Therefore, stabilising residual soil with plastic bottle shreds was a safe solution to the waste disposal problem and a cost-effective approach for stabilising weak soils.